CROSS-CULTURAL ADAPTATION, RELIABILITY, AND VALIDATION OF THE INTERNATIONAL PHYSICAL ACTIVITY QUESTIONNAIRE SHORT FORM IN LANGUAGES IN AFRICA: A SYSTEMATIC REVIEW (Journal of Biomedical Investigation, 2023)
Background: The African population consists of diverse cultures and languages whose first language is not English. To address the challenges of using the English version of the International Physical Activity Short Form (IPAQ-SF), encourage physical activity (PA) participation/research, and curb non-communicable diseases (NCDs) in developing countries in Africa, there is a need for cultural adaptation of the questionnaire.Aim of the study: This study aimed to conduct a Systematic Review on cultural adaptation, reliability and validation of the IPAQ-SF into African languages and to proffer probable reasons for differences between the versions.Materials and Methods: We searched PubMed, Google Scholar, and AJO from inception to August 14, 2022. Studies were recruited if they conducted a cultural adaptation, validation and reliability of IPAQ-SF into the African language. The data analysis included descriptive statistics, ANOVA, and Student’s t test using SPSS version 23, and a p
Keywords: international physical activity short form; cross-cultural adaptation; Africa; Validation; reliability